Online teaching and learning Mandarin Chinese / Nor Suraya Mariam Ahmad - Ahmad, Nor Suraya Mariam (2003)
Rapid development in information technology in recent years has made a great impact on teaching approaches and methodologies .The project of On-line Mandarin Chinese Teaching and Learning is designed for Language center of Mara University of Technology ,main campus, Shah Alam, with a particular focus on students who are taking Mandarin subject as their third languages. This project consists of five modules namely Access verification for authorized student and lectures, On-line exercise, Search Facilities, Simplified notes consist of grammar and vocabulary of Mandarin subject and Student interactivities. The main objective in building this website is to help student learn Mandarin subject. This project is being developed using JavaScript, VBScript, NJSTAR 2.0,Active Server Pages and Hypertext Mark-Up Languages and implemented using Web Development Methodologies where all task are transformed into several phases.